Emotion and Its Relationship to Acceptance, Food Choice, and Consumption: The New Perspective - Prinyawiwatkul, Witoon; da Cruz, Adriano Gomes (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Food is a source of nutrients but it also provides basic pleasure and aesthetic experiences. Acceptance, food choice, and consumption are affected by many factors, including both intrinsic and extrinsic factors and cues, as well as consumer characteristics. Food-elicited emotions are becoming a critical component in designing products that meet consumers' needs and expectations. Several studies have reported on the presence of emotional responses to food and the relationships of these to product acceptability, preference, and choice. This Special Issue brings together a small range of studies with a diversity of approaches that provide good examples of the complex and multidisciplinary nature of this subject matter.